The Influence Of Healthcare Practitioners' Attitudes, The Role Of Teamwork, And The Physical Environment On Patient Safety Culture In Jakarta Hospitals - Venny Venny; Erick Kristianto Adityatama; Aditia Prasetianto; Innocentius Bernarto (Eduvest - Journal of Universal Studies, 2024)
Patient safety is the primary goal in providing healthcare services. This can be realized by upholding a culture of patient safety, which refers to the values, beliefs, and behaviors held by hospital staff that prioritize patient safety. This study aims to determine the influence of healthcare practitioners' attitudes, the role of teamwork, and the physical environment on patient safety culture in Jakarta hospitals, as well as to formulate recommendations to improve patient safety culture in these hospitals. The study uses a quantitative method with a cross-sectional research design. Data for this study were collected through questionnaires, observations, and documentation studies. The population in this study consists of all healthcare practitioners in Jakarta hospitals, with sampling conducted using convenient sampling techniques. Data analysis techniques in this study include validity testing, reliability testing, and regression analysis using SPSS software. The results of the study indicate that healthcare practitioners' attitudes, the role of teamwork, and the physical environment have a positive and significant impact on patient safety culture in Jakarta hospitals.